PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELA IV TEMA 4 (BERBAGAI PEKERJAAN) MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Indriyani, Yuni; Afi Arianto, Pungkas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The problem of this research is the low learning outcomes of students, especially in Theme 4. Students still do not meet the completeness of the KKM value. The purpose of this study is to improve student learning outcomes through the Problem Based Learning Model in Learning Theme 4 Class IV Semester 1 SDN 1 Kebokura. The subjects of this study were fourth grade students of SDN 1 Kebokura. This research is a Classroom Action Research which lasts for two cycles consisting of planning, action, observation and reflection stages. The data collection technique in this research is a student evaluation test which consists of knowing the learning outcomes of students. Based on the research results obtained in this study, it can be concluded that the learning outcomes of Theme 4 students of class IV SDN 1 Kebokura can be increased by using the Problem Based Learning model. The increase in learning outcomes can be seen from the initial condition of the average score of 64.5 with a percentage of the number of students who completed 41.6%. In the first cycle there was an increase in the average value of 77.6 with the percentage of the number of students who completed 75%, with a target of 85%. Then in the second cycle there was an increase in the average score of 89.3 with the percentage of students who completed 100%, with a target. Based on the results of the study, it can be concluded that there is an increase in student learning outcomes in Theme 4 using the Problem Based Learning model.